2011
DOI: 10.1260/1708-5284.8.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of Reinforced Concrete Columns with Fiber Reinforced Polymer Bars

Abstract: In this paper, the results of an analytical investigation on the behavior of RC columns reinforced with fiber reinforced polymer bars FRP are presented and discussed. Nonlinear finite element analysis on 10column specimens was achieved by using ANSYS software. The nonlinear finite element analysis program ANSYS is utilised owing to its capabilities to predict either the response of reinforced concrete columns in the postelastic range or the ultimate strength of a reinforced concrete columns reinforced by FRP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The increase of main FRP reinforcement ratio boosts the ductility of cross section which has a significant effect on ultimate strain (to 19%) and ultimate loads (to 22%) of columns. Study results of Ehab M. Lotfy [11] indicated that, with the main reinforcement ratio up to 1.7%, load-carrying capacity and reinforcement ratio follows a linear trend.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase of main FRP reinforcement ratio boosts the ductility of cross section which has a significant effect on ultimate strain (to 19%) and ultimate loads (to 22%) of columns. Study results of Ehab M. Lotfy [11] indicated that, with the main reinforcement ratio up to 1.7%, load-carrying capacity and reinforcement ratio follows a linear trend.…”
Section: Introductionmentioning
confidence: 98%
“…In the previous researches by Alsayed et al [2], Luca et al [4], Ehab M. Lotfy [11], Tobbi et al [22], Mohammad Z. Afifi et al [14], Mohamed et al [13], Richa Pateriya1 et al [17], Muhammad N. S. et al [15], Jianwei Tu et al [23], it was showed that, when replacing the longitudinal steel bars with the FRP bars by the same amount, the axial load-carrying capacity of FRP concentrically RC columns decreases by 13%-16%. In FRP RC columns, FRP bars contribute about 3%-10% of the total load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Few experimental studies have been conducted to investigate the behaviour of the concrete column reinforced with GFRP under concentric loading [2][3][4][5][6][7][8][9]. It was concluded that columns reinforced with GFRP bars behave in the same manner as those reinforced with steel bars.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed about 10 percent strength reduction in the GFRP reinforced columns from cases with steel reinforcement. Short confined concrete cylinders with different spacings (10,20,35, and 50 mm) of aramid spiral stirrups were studied by Leung and Burgoyne [5]. The experimental results showed that the peak load capacity of test cylinders decreased with the spiral pitch.…”
mentioning
confidence: 99%
“…Also, a small increase in the core confinement, strength, and stiffness of tested columns was achieved by decreasing the pitch of spiral warps. The structural performance of square concrete columns internally reinforced with GFRP rebars was evaluated under axial compressive load in [10]. The ductility increased with the main reinforcement ratios, rapidly with small ratios but the effects were quite low for large reinforcement ratios.…”
mentioning
confidence: 99%